A new species of Waitea described and illustrated based on morphology and phylogeny from Western Ghats, India - Rana, Shiwali; Singh, Sanjay K. (Phytotaxa, 2025)
A novel species, Waitea lakhanpalii, is established to accommodate an interesting basidiomycetous fungus with corticoid, thin, and effused fruiting bodies found growing on dead wood in the Kolhapur region of Maharashtra, India. The identification of this strain was determined based on the morphological characters and phylogenetic analysis of internal transcribed spacer region (ITS) and 28S large subunit (nLSU) sequence data. The detailed taxonomic descriptions, cultural and microscopic images, and phylogenetic tree are presented for the new taxon. The sequencing data of this isolate exhibited substantial distinctness from the previously discovered species of Waitea and thus created a unique and distinct clade.